(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
Based on the analysis of environmental and social problems, a map containing the recorded albarradas was elaborated from Cacheli Grande y Miraflores, in Ventanas Parish, on the coast of Ecuador. The largest albarrada is of 25 m long, the average size is of 10 m and the smallest is of 6 m long, the deepest are of 8 m. Of those albarradas, 81% were built as water supply and 3% for recreational purposes. A photo monitoring of earthworks of interest was performed in the field and result tests were conducted, as well. From the social and economical viewpoints, it was established that 75% of the partners base the economic activity on agriculture, and that those are independient in relation to employments; on the environmental component was verified as modern albarradas influence on shaping landscapes, providing of good quality water for agricultural crops, and on the normal course of rivers while flowing to form springs with native plants. The benefits of the albarradas are groundwater recharge, regulating hydric erosion in some areas as well as the clogging by sedimentation. The surrounding vegetation benefits the agro ecosystem providing moisture to the soils.